Optimal path planning for electric vehicle travel time based on Dijkstra - Yang, Jiajia; Cai, Bin; Li, Xiaohui; Ge, Rongxianng (Chinese Control and Decision Conference, 2023)
To alleviate the environmental pollution caused by traditional fuel vehicles, electric vehicles have started to develop on a large scale and gradually replace traditional fuel vehicles. However, the limited mileage of electric vehicles, road traffic conditions and the status of charging stations affect the path planning of users. Therefore, to improve the travel efficiency of users using EVs, this paper proposes a path algorithm for optimal travel time based on Dijkstra algorithm. It takes the characteristics of EVs, road traffic conditions, and the status of charging stations into account to formulate the weight in Dijkstra algorithm. Then it constructs a binary sort tree to reduce the path search efficiency furtherly. Simulation results show that the proposed optimal path algorithm can plan the travel path with optimal time for users.